A critical discourse analysis of the representation of Donald Trump in the Guardian / Zainab Hamzah - Zainab, Hamzah (2012)
Employing Ruth Wodak’s Discourse-Historical Approach (Wodak 2001), this research report analyzes the construction of negative-other representation of Donald Trump and his Golf Complex project in Balmedie, Scotland by The Guardian online. The e-news articles are examined for the strategies that are employed to construct a negativeother representation of Donald Trump, and the ways these strategies are linguistically realized. The ensuing findings reveal that eventhough The Guardian successfully constructs a negative-other representation of Donald Trump, his success in getting the planning permission for his golf project shows this hegemonic influence and power over the people of Scotland.